HIBAH BINA DESA PENERAPAN TEKNOLOGI PENGOLAHAN ECENG GONDOK SEBAGAI PAKAN TERNAK DAN INDUSTRI KERAJINAN RUMAH TANGGA DI KELURAHAN LEMPAKE - Nursyam Nursyam; Akmal Dzuhri; Nova Andreanto Putro; Ratna Ratna; Lulu Khizanatusani; Sri Maryati; Luthfika Zyahratul Ula; Nirmala Anggraini; M. Alam Syah; Riyo Wijaya; Fauzin Fauzin; Mujiantoro Mujiantoro; Emillia Poni Yang Dalah; Marianus Ermen; Fitri Ismiyati Ramadani; Arif Ismanto (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
The aim of the Village Development Grant Program is to make efforts to empower the Lempake village community to use water hyacinth processing technology as animal feed and home industry in order to reduce sedimentation of Benanga reservoirs and increase the productivity of the community of Lempake village. Factors that trigerring this activity are the low of knowledge and skill data of comunity to optimize the potention of water hyacinth that become one of the keys in the reservoir in the kelurahan where the activity is located. Target Activities This Village Development Grant is a PKK group from the Lempake Village and the Subur Livestock Group. The main method in this activity is training and monitoring. Water hyacinth processing training produces several types of crafts (bags, tissue boxes and pillows) and the formation of community business groups, Egona Mulawarman. Meanwhile, to train feed cattle, water hyacinth using to make silage. The working relationships that exist include the City of Samarinda Industry Agency, and the Samarinda City Agriculture Service.Keywords : Empowerment, Water Hyacinth, Village Development Grants Program, handicrafts and silage.